Inspection method development for 3D printed components in aerospace industries - Tan, Yong Han (2016)
In order to improve manufacturing quality and in the industry’s continual efforts to ensure public safety, components and structures in the aerospace industry are commonly inspected for early detection of any forms of defects or faults which may compromise overall structural integrity. Non Destructive Testing or in short, NDT, currently presents sound advantages such as leaving the test subjects undamaged after inspection and fit for use immediately if within specification. In experimental NDT, available measurement data are usually used in order to gain clues, patterns or trends that may surface during the inspection process. And this clues includes possible representatives of structural modification such as cracks, porosities and even shifted layers. In this paper, comparisons between the five main stream NDT methods namely; Liquid penetrant (LP), Ultrasonic testing (UT), Magnetic particle inspection (MPI), Eddy current (EC) and Radiography, will be done with respect to specified 3D printed aerospace material(s) such as the commonly used aluminium alloys found in large quantities in commercial aircraft example the Boeing series airliners. Parts of this report will also feature the fabricating processes of a SLS (Selective laser Sintering) 3D printer. These methods are presented to investigate critical flaw-structure configuration, mainly focusing on sub surface defects in metallic parts. Proposed procedures may exploit and employ fuzzy logic. In conjunction with the evaluation and fabrication processes, ranking and selection of the “Best NDT method” for inspection on 3D printed aerospace parts will be chosen.